2018
DOI: 10.1097/ccm.0000000000003148
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of Unstructured Clinical Text Improves Early Prediction of Death or Prolonged ICU Stay*

Abstract: Variables extracted from unstructured clinical text from the first 48 hours of hospital admission using natural language processing techniques significantly improved the abilities of logistic regression and other machine learning models to predict which patients died or had long ICU stays. Learning health systems may adapt such models using open-source approaches to capture local variation in care patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 44 publications
0
63
0
2
Order By: Relevance
“…Recently, Weissman et al 36 studied the feasibility of incorporating clinical free text into a model to predict the combined outcome of mortality or prolonged length of stay, but their analysis was limited to a single institution, so they were not able to assess generalizability. Moreover, Weissman et al 36 found only very small marginal gains in predictive performance when using more complex machine learning methods, namely gradient boosting, over regularized logistic regression, as we used here.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Weissman et al 36 studied the feasibility of incorporating clinical free text into a model to predict the combined outcome of mortality or prolonged length of stay, but their analysis was limited to a single institution, so they were not able to assess generalizability. Moreover, Weissman et al 36 found only very small marginal gains in predictive performance when using more complex machine learning methods, namely gradient boosting, over regularized logistic regression, as we used here.…”
Section: Discussionmentioning
confidence: 99%
“…Frost et al [23], using used text fields from over 43,000 patients to, predict risk of frequent emergency department visits and high system costs with a Cstatistic of 0.71 and 0.76, respectively. Weissman et al [24] showed that inclusion of unstructured text along with structured data improved prediction of death in the ICU by using four different predictive modeling approaches. Text-mining of clinical notes has been used to identify postoperative complications in veterans [25] but, to the best of our knowledge, has not been utilized for predicting postoperative surgery outcomes in children.…”
Section: Methodsmentioning
confidence: 99%
“…Frost et al [23], using used text fields from over 43,000 patients to, predict risk of frequent emergency department visits and high system costs with a C-statistic of 0.71 and 0.76, respectively. Weissman et al [24] showed that inclusion of unstructured text along with structured data improved prediction of death in the ICU by using four different predictive modeling approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Using neural networks, classification algorithms can be constructed for identification of the most important terms in physician notes, which then can be used to construct ML models to predict outcomes such as mortality in the surgical ICU. 39 One such model, called Early Mortality Prediction for Intensive Care Unit patients, has been shown to outperform traditional scoring systems such as acute physiology and chronic health evaluation (APACHE) and sequential organ failure assessment (SOFA) despite missing values within the training datasets. The area under the curve (AUC) is 0.82 ± 0.04 compared with the traditional scoring systems which range from 0.54 to 0.65.…”
Section: Predictive Analyticsmentioning
confidence: 99%